1996
DOI: 10.1103/physreva.53.1791
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of damping theory for cavities with mirrors of finite transmittivity

Abstract: Standard damping theory is generalized to incorporate the effects of finite mirror transmittivity. The correction to the standard Langevin equation for the quasimode annihilation operator is determined in first order in the transmittivity of the mirrors. From the Langevin equation an effective master equation is derived. As an example, we study the decay of a single two-level atom at a fixed position in a nonideal cavity. For this case we find a modification of the damped Rabi oscillations, which depends on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…(2.6). Therefore, one can expand the mode functions around the resonance frequency and obtain the so-called single mode approximation result [32,33,34]:…”
Section: Atom-field Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2.6). Therefore, one can expand the mode functions around the resonance frequency and obtain the so-called single mode approximation result [32,33,34]:…”
Section: Atom-field Interactionmentioning
confidence: 99%
“…In Sec. V, the generation of entanglement is studied for two cases with different input states, namely, a cavity photon [32,33,34] and an arbitrary injected photon. We conclude the main features of our scheme in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…If the mirror transmittivity becomes finite, the damping terms get a more complicated structure, owing to the interplay of the loss mechanism and the intracavity interaction. The "generalized" master equation that arises by accounting for these enhanced losses has been established recently [3]. In applying this equation to the time evolution of a decaying atom in a cavity we have found that the effects of increased losses can be quite substantial [4].…”
Section: Introductionmentioning
confidence: 98%
“…The same configuration has been assumed in deriving the generalized master equation in [3]. Quite different loss effects can be expected if the bath is in a different state, for instance in a squeezed vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the QNT model of a cavity without unwanted noise includes the quantum Langevin equation (1), the input-output relation (4) and the constraints for the c-number coefficients (8)(9)(10). In particular, the constraint (8) describes the relation between the cavity decay rate and the coefficient T (c) .…”
Section: Idealized Cavity Modelmentioning
confidence: 99%